The Strengthening the Value of Religious Moderation through Learning of Faith and Ethics at MTs Nasyrul Ulum Tempuran Central Lampung - Padila, Amalia; Syafe'i, Imam; Akhmansyah, Muhammad (International Journal on Advanced Science, Education, and Religion, 2024)
This article discusses the strengthening of moderation values ​​through learning of creed and morals at MTs Nasyrul Ulum Tempuran Lampung Tengah. Religious moderation is a central issue that is being intensively socialized by the Ministry of Religion as a form of realizing a harmonious Indonesia. Therefore, strengthening religious moderation through educational institutions with a learning process is very appropriate, the values ​​of religious moderation are instilled through the Creed and Morals learning process. This study uses a qualitative method with a type of field research, the author conducted research directly through observation, interviews, and documentation. The results of the study show that: (1) Strengthening moderation values ​​through Creed and Morals learning at MTs Nasyrul Ulum Madrasah plays a very important role in shaping students' character and attitudes. (2) Strengthening Religious Moderation Values ​​Through Creed and Morals Learning Planning at MTs Nasyrul Ulum has learning objectives, learning materials, learning methods, and learning activities designed in the syllabus and RPP containing moderate values, tolerance, respect for differences and mutual cooperation. (3) Strengthening the Value of Religious Moderation Through Evaluation of Beliefs and Ethics at Mts Nasyrul Ulum Tempuran Lampung. With a planned and systematic evaluation, MTs Nasyrul Ulum can effectively measure and strengthen the value of religious moderation among students. Evaluations that include various methods and involve many parties will provide a more complete picture of how students internalize the values ​​of moderation in everyday life, as well as foster their awareness of the importance of tolerance in a multicultural society.